2011
DOI: 10.1167/10.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Natural cross-modal mappings between visual and auditory features

Abstract: The brain may combine information from different sense modalities to enhance the speed and accuracy of detection of objects and events, and the choice of appropriate responses. There is mounting evidence that perceptual experiences that appear to be modality-specific are also influenced by activity from other sensory modalities, even in the absence of awareness of this interaction. In a series of speeded classification tasks, we found spontaneous mappings between the auditory feature of pitch and the visual fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

58
360
5
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(428 citation statements)
references
References 29 publications
58
360
5
5
Order By: Relevance
“…The results obtained in our study also go further in terms of explaining the origin of the spatial mapping of pitch which underlies a well-documented series of effects (e.g. Evans & Treisman, 2010;Patching & Quinlan, 2002;Rusconi et al, 2006). They challenge the idea of a general, amodal spatial representation of pitch shared across all modalities, along with other spatial representations of magnitudes (e.g.…”
Section: General Discussion and Conclusionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results obtained in our study also go further in terms of explaining the origin of the spatial mapping of pitch which underlies a well-documented series of effects (e.g. Evans & Treisman, 2010;Patching & Quinlan, 2002;Rusconi et al, 2006). They challenge the idea of a general, amodal spatial representation of pitch shared across all modalities, along with other spatial representations of magnitudes (e.g.…”
Section: General Discussion and Conclusionsupporting
confidence: 79%
“…they were told that a high pitch sound is more likely to be correlated with a high visual target, Chiou & Rich, 2012) or at least trained by using the predicates 'high' and 'low' to describe the sounds (Evans & Treisman, 2010). Here we purposively provided only neutral information about these characteristics, to avoid biasing participants on the classification of the tactile stimuli.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Previous experimental evidence demonstrates that human adults are sensitive to these relationships, even within age and sex morphs [11,[16][17][18]. For instance, experimentally lowering F 0 and formant dispersion in young men's voices increases the speaker's perceived masculinity, size and age [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the existence of a relationship between auditory pitch and different visual features, such as spatial elevation (Ben-Artzi & Marks, 1995;Bernstein & Edelstein, 1971;Evans & Treisman, 2010;Melara & O'Brien, 1987;Patching & Quinlan, 2002;Rusconi, Kwan, Giordano, UmiltĂ , & Butterworth, 2006), brightness (Ludwig, Adachi, & Matzuzawa, 2011;Marks, 1987) or lightness (Hubbard, 1996;Marks, 1987;Martino & Marks, 1999;Melara, 1989;Mondloch & Maurer, 2004), size (Evans & Treisman, 2010;Gallace & Spence, 2006;Mondloch & Maurer, 2004), angularity of shape (Marks, 1987), direction of movement (Clark & Brownell, 1976), and even spatial frequency (Evans & Treisman, 2010).…”
mentioning
confidence: 99%